2017
DOI: 10.1111/jam.13399
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic metabolism in the genusLactobacillus: impact on stress response and potential applications in the food industry

Abstract: SummaryThis review outlines the recent advances in the knowledge on aerobic and respiratory growth of lactic acid bacteria, focusing on the features of respiration-competent lactobacilli. The species of the genus Lactobacillus have been traditionally classified as oxygen-tolerant anaerobes, but it has been demonstrated that several strains are able to use oxygen as a substrate in reactions mediated by flavin oxidases and, in some cases, to synthesize a minimal respiratory chain. The occurrence of genes related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
90
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 63 publications
3
90
1
3
Order By: Relevance
“…We found that PDH played the predominant role in the aerobic conversion of pyruvate to acetate and POX had a secondary role. L. brevis, having both functional PDH and POX under aerobic conditions, was different from the other lactobacilli reported previously (20).…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…We found that PDH played the predominant role in the aerobic conversion of pyruvate to acetate and POX had a secondary role. L. brevis, having both functional PDH and POX under aerobic conditions, was different from the other lactobacilli reported previously (20).…”
Section: Discussioncontrasting
confidence: 90%
“…The extra energy provided in aerobic growth might be produced in three ways, as follows. (i) Oxygen repressed the expression of alcohol dehydrogenase (20) and thus shifted ethanol production to acetate. (ii) When glucose levels were substantial, pyruvate was channeled to acetyl-CoA followed by acetate production, instead of reduction of pyruvate to lactate (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations